Functional characterization of the Serine acetyltransferase family genes uncovers the diversification and conservation of cysteine biosynthesis in tomato - Liu, Danmei; Li, Min; Guo, Ting; Lu, Juanjuan; Xie, Yafang; Hao, Yuan; Wang, Longdan; Zhao, Dan; Zhang, Liping; Liu, Zhiqiang; Jin, Zhuping; Pei, Yanxi (Frontiers in Plant Science, 2022)
Sulfur-containing compounds are essential for plant development and environmental adaptation, and closely related to the flavour and nutrition of the agricultural products. Cysteine, the first organic sulfur-containing molecule generated in plants, is the precursor for most of these active substances. Serine acetyltransferase (SERAT) catalyzes the rate-limiting step of its formation. However, despite their importance, systematic analyses of these enzymes in individual species, especially in economically important crops, are still limited. Here, The SERAT members (SlSERATs, four in total) were identified and characterized in tomato. Phylogenetically, the four SlSERAT proteins were classified into three subgroups with distinct genomic structures and subcellular localizations. On the function, it was interesting to find that SlSERAT3;1, possessed a high ability to catalyze the formation of OAS, even though it contained a long C-terminus. However, it retained the essential C-terminal Ile, which seems to be a characteristic feature of SERAT3 subfamily members in Solanaceae. Besides, SlSERAT1;1 and SlSERAT2;2 also had high activity levels and their catalyzing abilities were significantly improved by the addition of an OAS-(thiol)-lyase protein. At the transcriptional level, the four SlSERAT genes had distinct expression patterns during tomato plant development. Under abiotic stress conditions, the chloroplast-localized SlSERATs were the main responders, and the SlSERATs adopted different strategies to cope with osmotic, ion toxicity and other stresses. Finally, analyses in the loss-of-function and overexpression lines of SlSERAT1;1 suggested that function redundancy existed in the tomato SERAT members, and the tomato SERAT member was ideal target for S-assimilation manipulating in molecular breeding.